Penentuan Batuan Alas dan Batuan Penyekat berdasarkan Metode Geolistrik Konfigurasi Dipole-Dipole pada Telaga Gesing, Pucanganom, Kabupaten Gunung Kidul - Al Hussein Flowers Rizqi; Fatimah (Retii, 2020)
The presence of dolines at Gunung Sewu Karst are relatively has many variations. The shape and dimention of dolines could be affected by the surrounding rocks. This research is focused on identify of seal rock at Gesing doline, Pucanganom, Gunung Kidul based on geological surface and geological subsurface using geolectrical with dipole-dipole configuration. The geological surface conducted in detail observation of outcrop in geological field. The subsurface geological data conducted to delineated tha seal rock layer based on result of processing from Res 2 dinv software. The result of geological data such as the presence of tuffaceous layer at base of doline that has a direction layer at N 30oE / 8o. The result of petrographical analysis showed that the rock contained the glass composition about 73% that rock named by Vitric Tuff. The result of paleontological analysis showed the rock age at N 5 (Early Miocene) that could be correlated to regional stratigraphy with Semilir Formation. The presence of tuffaceous at base of doline could be interpreted as seal rock of Gesing doline. Keyword: Seal rock, tuff, Gesing Doline, Gunung Kidul, geoelectrical